The Shapes of Modernity: On the Philosophical Roots of Anthropological Doctrines - Leavitt, John (Culture, 1991)
While more and more anthropologists are conducting research on and/or in contemporary Western societies, little attempt has been made to characterize modern Western culture as such. The philosophies of Descartes and Leibniz, in particular, may be read as articulating ways of organizing experience that are typical of modernity. These “thought-forms” are still powerful both in everyday experience and in the social sciences, including anthropology. An example is drawn from the anthropology of the emotions; an alternative is suggested based on the heterodox philosophy of Spinoza.